2019
DOI: 10.1029/2019jb017602
|View full text |Cite
|
Sign up to set email alerts
|

Finite‐Frequency Inversion of Cross‐Correlation Amplitudes for Ambient Noise Source Directivity Estimation

Abstract: We present a new method for determining the azimuthal variation of ambient noise sources, which combines the computational speed and simplicity of traditional approaches with the rigor of waveform-inversion-based approaches to noise source estimation. This method is based on a previously developed theoretical framework of sensitivity kernels for cross-correlation amplitudes. It performs a tomographic inversion for ambient noise sources on the Earth's surface and is suitable for small-(local-) scale studies. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…power spectral densities of seismic noise, can be modeled for arbitrary noise source distributions. Finally, it can be utilized for noise source inversion when no updates to the Earth structure model are required, similar to the pioneering study by Nishida and Fukao (2007), who inverted observed cross-correlations for source distribution of the Earth's hum, and as performed by Ermert et al (2017); Xu et al (2018Xu et al ( , 2019 and Datta et al (2019).…”
Section: Possible Applicationsmentioning
confidence: 95%
See 3 more Smart Citations
“…power spectral densities of seismic noise, can be modeled for arbitrary noise source distributions. Finally, it can be utilized for noise source inversion when no updates to the Earth structure model are required, similar to the pioneering study by Nishida and Fukao (2007), who inverted observed cross-correlations for source distribution of the Earth's hum, and as performed by Ermert et al (2017); Xu et al (2018Xu et al ( , 2019 and Datta et al (2019).…”
Section: Possible Applicationsmentioning
confidence: 95%
“…CC BY 4.0 License. pre-calculated Green's functions have recently been applied to a variety of seismological problems, such as source inversion of earthquakes (Dahm et al, 2018;Fichtner and Simutė, 2018), landslides (Gualtieri and Ekström, 2018) and ambient noise (Ermert et al, 2017;Datta et al, 2019). Although the generation of such databases themselves often requires HPC resources, they can be shared to provide access to the results of costly wave propagation simulations to users without access to those resources.…”
Section: Using Waveform Databases For Rapid Realistic Cross-correlatmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical models of noise auto-and crosscorrelations allow us to probe this assumption and eventually circumvent it (Halliday and Curtis, 2008;Fan andSnieder, 1598 L. Ermert et al: Noise modeling andinversion 2009;Cupillard and Capdeville, 2010;Kimman and Trampert, 2010;Fichtner, 2014;Stehly and Boué, 2017;Delaney et al, 2017). While the number of applications based on the Green's function assumption is large and rapidly increasing (Nakata et al, 2019), only a modest number of studies have presented models of ambient noise cross-correlations themselves, i.e., numerical evaluations of cross-correlations due to distributed noise sources rather than models of Green's functions (e.g., Nishida and Fukao, 2007;Tromp et al, 2010;Hanasoge, 2013a;Basini et al, 2013;Ermert et al, 2017;Sager et al, 2018bSager et al, , 2020Datta et al, 2019;Xu et al, 2018Xu et al, , 2019.…”
Section: Motivationmentioning
confidence: 99%